Gut–Lung Axis: Microbial Crosstalk in Pediatric Respiratory Tract Infections - Zhu, Wenxia; Wu, Yilin; Liu, Hui; Jiang, Caini; Huo, Lili (Frontiers in Immunology, 2021)
The gut microbiota is an important regulator for maintaining the organ microenvironment through effects on the gut-vital organs axis. Respiratory tract infections are one of the most widespread and harmful diseases, especially in the last 2 years. Many lines of evidence indicate that the gut microbiota and its metabolites can be considered in therapeutic strategies to effectively prevent and treat respiratory diseases. However, due to the different gut microbiota composition in children compared to adults and the dynamic development of the immature immune system, studies on the interaction between children's intestinal flora and respiratory infections are still lacking. Here, we describe the changes in the gut microbiota of children with respiratory tract infections and explain the relationship between the microbiota of children with their immune function and disease development. In addition, we will provide perspectives on the direct manipulation of intestinal microbes to prevent or treat pediatric respiratory infections.